A Case Study of Tax Avoidance in Food and Beverage Companies from the Aspects of Corporate Social Responsibility and Company Size: Studi Kasus Penghindaran Pajak Pada Perusahaan Pangan dan Minuman Dari Aspek Corporate Social Responsibility dan Ukuran Perusahaan - Siswanti Siswanti; Untung Wahyudi; Khojanah Hasan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
This case study aims to analyze the influence of corporate social responsibility (CSR) and company size on tax avoidance in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2023 period. The study was conducted using a quantitative approach with secondary data. The data sample consisted of 148 companies selected using a purposive sampling method. Data were analyzed using descriptive analysis, multiple linear regression, and panel data regression supported by classical assumption tests, multicollinearity tests, and heteroscedasticity tests using EViews 10 software. The results of the study indicate that CSR and company size simultaneously have a significant effect on tax avoidance. Partially, CSR has a negative effect on tax avoidance, while company size has a positive effect on tax avoidance. These findings emphasize the importance of integration between CSR and fiscal compliance in corporate governance practices. These results can be applied as a basis for formulating strategies to improve corporate integrity and accountability in supporting the national tax system.